Formação docente em contexto neoliberal: projetos e disputas nas políticas educacionais - Sousa, Maraiane Pinto de (2021)
The Ministry of Education (MEC) released on 2018 the Common National Base proposal for the Starting and Continuous Training of Teacher of the Basic Education (BNC-F), which can be configured as another document of adaptation to the needs from BNCC, guided by competences. The discussion we brought up about the Base is its confluence on the teachers training, considering the practical aspect of such professionals and some questionings which were placed as imperatives regarding the challenges that this policy intends. We also consider the process of construction of a new curriculum and its agents involved as the private sector, international organizations, social institutions and organizations and OCDE. The targeting of this work intended to discuss as central question: how the starting training of teachers configured inside educational policies after the approval of the BNCC? For that, the general goal of this dissertation was to analyze the starting training of teachers and its reformulation after the BNCC. We also elected as specific goals: a) identifying changes of legislation concerning the starting training of teachers; b) investigating the teacher training configuration and the involved agents and c) analyzing the context of influence on the teachers training and its ramifications. Analytically, we took support on the studies of Arroyo (2011); Ball (2014); Freitas (2018); Apple (2003,2011), Aguiar and Dourado (2019); Rocha (2019), just like in other authors whose works are reference to our research theme. In terms of methodology, our work is based on the contributions of Gonsalves (2011), Richardson (2017), Santos (2010), Michel (2015) and Cellard (2008), which characterize the research as qualitative and bibliographic, adding the documental analyses too. In order to provide arguments, we used the policy Cycle by Stephen Ball and collaborators (992, 1994). Thus, the analyses happen from the context of influence and text production of the formative bases, the pack of reforms, global agenda, national curriculum and neoliberal context in the education. That said, what we intended was the analyses on how the teachers training was proposed and what conception of training it is being formulated. The context of the practice made possible to analyze, from observations and works which are linked with the research theme, how this came up. Adding what has been said to all devices which we lean on, attempting to the global, social and political context, the terms used, the agents that are involved in the development of the policy and the effects of the political texts in the practice, talking about modifications brought up from them. We comprehend, from our analyses on what Rocha (2019) highlights, that the BNCC is a normative curriculum that follows a rationalist and thoughtless logic, causing effects as teacher standardization, significate loss of the teacher autonomy, projection of technique and performer teachers, specifically, projection of a teacher acting, a curricular organization. The standardization of the contents and methods through the BNCC delimits the work of the teachers.